Python Programming for Beginners : Hands-on (Online Lab) - Brain, www.GlobalETraining.com (Packt Publishing, 2021)
Dive deep into the concepts of object-oriented programming (OOP) and become a professional in creating classes and writing clean Python code About This Video Get to grips with the four pillars of object-oriented programming (OOP) Find out the role of OOP concepts in Python Learn how to create classes using the principles of OOP In Detail From DevOps to cloud computing and data science, Python programming language is used in almost every field of computer science. But what happens when you use the principles of object-oriented programming (OOP) in Python? Find out in this course. The course starts with an introduction to OOP concepts and then gradually proceeds towards giving you a detailed insight into OOPs concepts. You will find out what is abstraction, encapsulation, inheritance, and polymorphism in OOP in detail. By the end of this course, you will be well-versed with Python OOP and will have developed the skills to write clean Python code and take your Python skills to the next level.